Markers of metabolic syndrome in obese children before and after 1-year lifestyle intervention program - Pedrosa, C (2011)
Excess weight may be related to the development of adverse cardiometabolic risk factors in children. The aim of this study was to evaluate the effect of a lifestyle intervention program (nutrition and exercise counseling) on anthropometric parameters and metabolic syndrome (MS) components in Portuguese overweight/obese children. A total of 83 overweight/obese children aged 7-9 years were assigned to a 1-year individual or group-based treatment (GT); 61 children (z-score BMI (zBMI): 1.93 +/- A 0.28; 27 boys and 34 girls) completed the program. Anthropometric and biochemical parameters were assessed at baseline, at 6 months and at 1 year. The overweight/obese children, compared to normal-weight ones, presented significantly higher blood pressure, total-cholesterol, total-cholesterol/high density lipoprotein cholesterol (HDL) ratio, triglycerides, Apolipoprotein B and C-reactive protein levels, while HDL and Apolipoprotein A-I were significantly lower. At baseline, the prevalence of MS was 16.4% in overweight/obese and 0% in normal-weight children. The number of components of MS was significantly higher in children with higher zBMI. Lifestyle intervention led to a significant improvement in zBMI, waist circumference/height ratio, HDL, triglycerides, Apolipoprotein A-I, and Apolipoprotein B levels. The prevalence of MS decreased to 14.8%. The GT intervention seems to be more successful, with a significant decrease in zBMI and an increase in HDL and a lower drop-out rate. Overweight/obese children have multiple risk factors associated with the MS. Lifestyle intervention, both individual and group-based treatment, led to an improvement in the degree of overweight/obesity and in MS components.